Research and Teaching for Sustainability in the RUDN University - Vladimir Filippov; Elena Savenkova; Margarita Redina (Universitas Diponegoro, 2024)
More than 30 years ago, the participation of RUDN in the Earth Summit in Rio became an important moment in the university’s history: it was decided to create the first comprehensive ecological faculty in Russia. Now half of the history of our university is also the history of environmental education in Russia. During this time, more than 10,000 ecologists and hundreds of specialists in other sustainability areas were trained. Almost all programs at the university include aspects of sustainability. Over 15 MOOCs and 10 interdisciplinary courses on relevant aspects have been developed. Annually, over 1,000 specialists improve their skills in various aspects of sustainability. An extensive research program in the areas of environmental safety and sustainability includes only in recent years: a program on environmental safety of transport (a part of the Federal project “Clean Air”); expert work on the implementation of BATs. In 2021, Russia’s first Body for the Validation and Verification of Greenhouse Gases was successfully accredited in the university. More than 100 students are annually involved in the campus environmental monitoring program. Since 2022, the university presents a sustainability report. The environmental policy is presented on the university website and has been successfully implemented since 2017. We are confident: the role of the university is the formation of personality, the promotion of the sustainability ideas on the example of its home university.